Investigation of ErbB-2 Overexpression on Patients with Gastric Cancer in Eastern Anatolia of Turkey - Habib EMRE,; Salim Başol TEKİN,; Hasan DOĞAN,; Kerim ÇAYIR,; Mehmet BİLİCİ,; Sare ŞİPAL,; İbrahim PİRİM, (Turkish Journal of Gastroenterology, 2019)
-